Tractate Qiddušin - Guggenheimer, Heinrich W. (Studia Judaica, 2008)
This volume concludes the edition, translation, and commentary of the third order of the Jerusalem Talmud. The pentateuchal expression lqkh 'ššh "to take as wife" is more correctly translated either as "to acquire as wife" or "to select as wife". The Tractate Qiddušin deals with all aspects of acquisition as well as the permissible selections of wives and the consequences of illicit relations.